Effect of counterpart metals in carbon-supported Pt-based catalysts prepared using radiation chemical method. (April 2017) - Okazaki, Tomohisa; Seino, Satoshi; Matsuura, Yoshiyuki; Otake, Hiroaki; Kugai, Junichiro; Ohkubo, Yuji; Nitani, Hiroaki; Nakagawa, Takashi; Yamamoto, Takao A.
Abstract: The process of nanoparticle formation by radiation chemical synthesis in a heterogeneous system has been investigated. Carbon-supported Pt-based bimetallic nanoparticles were synthesized using a high-energy electron beam. Rh, Cu, Ru, and Sn were used as counterpart metals. The nanoparticles were characterized by inductively coupled plasma atomic emission spectrometry, transmission electron microscopy, X-ray diffraction, and X-ray absorption spectroscopy. PtRh formed a uniform random alloy nanoparticle, while Cu partially formed an alloy with Pt and the remaining Cu existed as CuO. PtRu formed an alloy structure with a composition distribution of a Pt-rich core and Ru-rich shell. No alloying was observed in PtSn, which had a Pt-SnO2 structure. The alloy and oxide formation mechanisms are discussed considering the redox potentials, the standard enthalpy of oxide formation, and the solid solubilities of Pt and the counterpart metals. Highlights: Carbon-supported PtRh, PtRu, PtCu, and PtSn nanoparticles were synthesized. Obtained structure varied with counterpart metal. The critical factors in determining the nanoparticle structure is revealed. Formation mechanism of nanoparticles using radiation chemical method is discussed.